The Downside of Self-Management: A Longitudinal Study of the Effects tf Conflict on Trust, Autonomy, and Task Interdependence in Self-Managing Teams - Langfred, Claus W. (Academy of Management Journal, 2007)
The very flexibility and adaptability that make self-managing teams effective can also be limiting and dysfunctional. I propose that self-managing teams may unintentionally restructure themselves inefficiently in response to conflict. Although detrimental consequences of conflict are normally considered as process-related, I explore possible structure-related effects. Specifically, I suggest that increased team conflict is associated with lower intrateam trust, which in turn may influence team structure by (1) reducing individual autonomy and (2) loosening task interdependencies in teams. This combination makes for a less than ideal team design. Longitudinal data from 35 self-managing teams support these expectations.